The prophylactic effect of probiotic enterococcus lactis IW5 against different human cancel cells - Nami, Yousef; Haghshenas, Babak; Haghshenas, Minoo; Abdullah, Norhafizah; Khosroushahi, Ahmad Yari (Frontiers, 2015)
Enterococcus lactis IW5 was obtained from human gut and the potential probiotic characteristics of this organism were then evaluated. Results showed that this strain was highly resistant to low pH and high bile salt and adhered strongly to Caco-2 human epithelial colorectal cell lines. The supernatant of E. lactis IW5 strongly inhibited the growth of several pathogenic bacteria and decreased the viability of different cancer cells, such as HeLa, MCF-7, AGS, HT-29, and Caco-2. Conversely, E. lactis IW5 did not inhibit the viability of normal FHs-74 cells. This strain did not generate toxic enzymes, including β-glucosidase, β-glucuronidase, and N-acetyl-β-glucosaminidase and was highly susceptible to ampicillin, gentamycin, penicillin, vancomycin, clindamycin, sulfamethoxazol, and chloramphenicol but resistant to erythromycin and tetracyclin. This study provided evidence for the effect of E. lactis IW5 on cancer cells. Therefore, E. lactis IW5, as a bioactive therapeutics, should be subjected to other relevant tests to verify the therapeutic suitability of this strain for clinical applications.